Low-Grade Uterine Endometrial Stromal Sarcoma: Prognostic Analysis of Clinico-Pathological Characteristics, Surgical Management, and Adjuvant Treatments. Experience From Two Referral Centers - Borella, Fulvio; Bertero, Luca; Cassoni, Paola; Piovano, Elisa; Gallio, Niccolò; Preti, Mario; Cosma, Stefano; Ferraioli, Domenico; Pace, Luca; Mariani, Luca; Biglia, Nicoletta; Benedetto, Chiara (Frontiers in Oncology, 2022)
Objective Low-grade uterine endometrial stromal sarcoma (LG-ESS) is a rare tumor characterized by an overall good survival but with indolent behavior and a variable risk of recurrence. There is no clear consensus on the optimal management of these tumors and no prognostic or predictive factors have been established. With this study, we evaluated the prognostic relevance of several clinical, surgical, and pathological features in patients affected by LG-ESS to identify risk factors of recurrence. Methods We retrospectively analyzed 52 cases with LG-ESS, treated from January 1st, 1994, to May 31st, 2020, in two referral centers. The relationship between LG-ESS recurrence and clinicopathological characteristics as well as surgical treatment was investigated. Risk recurrence and disease-free survival (DFS) were estimated by Cox regression and the Kaplan-Meier analysis, respectively. Results Of 52 patients with LG-ESS, 8 experienced recurrence (15%). The median follow-up was 100 months (SD ± 96, range: 15–336). Fragmentation/morcellation, tumor size, FIGO stage, higher mitotic count, presence of necrosis, and lymphovascular space invasion were related to recurrence. The surgical modality (laparotomic vs laparoscopic approach and hysterectomy with bilateral salpingo-oophorectomy vs local excision) and pelvic lymphadenectomy do not seem to alter the risk of recurrence. Even the different modalities of adjuvant therapy (hormonal therapy, radiotherapy, and chemotherapy) do not seem to harbor a prognostic role. Conclusions This data supports the avoidance of any morcellation if LG-ESS is suspected preoperatively. Tumor size, advanced FIGO stage, high mitotic count, necrosis, and LVSI seem to be useful in tailoring the adjuvant therapy, but these data need to be confirmed in larger prospective studies.